Meeting democracy : power and deliberation in global justice movements - Della Porta, Donatella, 1956-; Rucht, Dieter (Cambridge University Press, 2013)
An innovative study of the internal practices of deliberation and democratic decision-making in twelve Global Justice social movement groups.